HUBUNGAN LAMA MENDERITA DIABETES MELLITUS TIPE II DENGAN KEJADIAN KOMPLIKASI POLINEUROPATI DIABETIK DI WILAYAH KERJA PUSKESMAS ANTANG PERUMNAS KECAMATAN MANGGALA KOTA MAKASSAR - Ubo, Naharia La; khair, mukhlisah nurul (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2019)
Diabetic polyneuropathy is one of the complications illustrating the extent of peripheral nerve involvement and generally bilateral symmetrical distribution including sensory, motor and autonomic disorders. The aim of the study was to determine the long association of type II diabetes mellitus with the incidence of complications of diabetic polyneuropathy in the Work Area of the Antang Perumnas Health Center, Manggala District, Makassar City. This study was designed with an analytical descriptive method using a cross sectional design and using Chi Square Test. The sampling technique in this study uses Purposive Sampling. The results of the study were p = 0.004, there was a long association with type II diabetes mellitus with the incidence of diabetic polyneuropathy. The conclusion of this study was that there was a significant relationship between the duration of suffering from type II diabetes mellitus and the incidence of diabetic polyneuropathy. It is better if people with diabetes mellitus can maintain blood glucose control and do the best foot care in accordance with what is recommended by health workers and carry out healthy living behaviors with diabetes mellitus.